Growth Rate and Capsaicin Level of Curly Red Chili (Capsicum annum L.) on Biofertilizer and Biogas Sludge Application - Dwi Umi Siswanti; Melinda Fajar Lestari (UIN Sunan Gunung Djati Bandung, 2019)
Curly red chili (Capsicum annum L.) is widely cultivated us-ing inorganic fertilizers which causes high production costs. Chili is valued because of the level of spiciness. The level of spiciness of chili is determined by the level of capsaicin which is affected by nutrients in the growing media. The nutrient of the planting media can be fulfilled by degrading the growing media by microbes in organic fertilizer. One type of organic fertilizer containing degrading microbes is biofertiliz-er. Biofertilizer and biogas sludge is one of the organic fertilizers con-taining microbes and organic materials that are able to support nutri-ent levels of the planting medium. This study aimed to analyze growth parameters include chlorophyll content and measure capsaicin levels in curly red chili. Which given biofertilizer and biogas sludge in vari-ous dosage and determine the optimum dose of the fertilizer. The study was conducted at an agricultural demonstration plot in Wukirsari Vil-lage, Cangkringan, Sleman. The study design used RCBD (Randomized Complete Block Design), the data were analyzed by ANOVA (Analysis of Variance followed by Duncan’s Multiple Distance Test (DMRT) at the 95% confidence level. The highest growth parameters and capsa-icin content were obtained on curly red chili plants which were given biogas sludge 36 mL + biofertilizer 10 L / ha. The application of bi-ofertilizer and biogas sludge in various concentrations given has not been able to increase the average total chlorophyll content of curly red chili plants. Thus, it can be concluded that the most appropriate dose of curly red chili is 36 mL biogas sludge + 10 L bio fertilizer/ha